Acceptability of a vocational advice service for patients consulting in primary care with musculoskeletal pain: A qualitative exploration of the experiences of general practitioners, vocational advisers and patients. Issue 1 (February 2019) - Sanders, Tom; Wynne-Jones, Gwenllian; Nio Ong, Bie; Artus, Majid; Foster, Nadine
Aims: Using qualitative interviews, this study explored the experiences of GPs, vocational advisers and patients towards a new vocational advice (VA) service in primary care. Methods: This study was nested within the Study of Work and Pain (SWAP) cluster randomised controlled trial. The SWAP trial located a VA service within three general practices in Staffordshire. Interviews took place with 10 GPs 12 months after the introduction of the VA service, four vocational advisers whilst the VA service was running and 20 patients on discharge from the VA service. The data were analysed using the constant comparative method, which is a variation of grounded theory. Results: The key factors determining the acceptability and perceived effectiveness of the VA service from the perspective of the three groups of stakeholders were (1) the timing of referrals to the VA, (2) the perceived lack of patient demand for the service and (3) role uncertainty experienced by VAs. Conclusions: Early vocational intervention may not be appropriate for all musculoskeletal patients with work difficulties. Indeed, many patients felt they did not require the support of a VA, either because they had self-limiting work difficulties and/or already had support mechanisms in place to return to work. Future VA interventions may be better implemented in a targeted way so that appropriate patients are identified with characteristics which can best be addressed by the VA service .